2004
DOI: 10.1099/mic.0.27015-0
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic growth of the haloalkaliphilic denitrifying sulfur-oxidizing bacterium Thialkalivibrio thiocyanodenitrificans sp. nov. with thiocyanate

Abstract: Two strains of obligate chemolithoautotrophic sulfur-oxidizing bacteria were isolated from soda-lake sediments by enrichment culture with thiocyanate and nitrate at pH 9?9. The isolates were capable of growth with thiocyanate or thiosulfate as electron donor, either aerobically or anaerobically, and with nitrate or nitrite as electron acceptor. Cyanate was identified as an intermediate of thiocyanate oxidation, while sulfate, ammonia and dinitrogen gas were the final products. The anaerobic growth on thiocyana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 28 publications
3
74
1
Order By: Relevance
“…Kinetic constants were higher in MM for the lowest initial concentrations of thiocyanate, whereas the opposite behaviour was observed for concentrations higher than 4,000 mg L -1 . Degradation rates between 1 and 87 mg (Lh) -1 were reported for the biodegradation of thiocyanate by specific microorganisms [6,18,19,24] similar to the degradation rates obtained in this work. In fact, only Acremonium strictum showed higher removal rates [19].…”
Section: Utilization Of Nitrogen and Sulphur From Thiocyanatesupporting
confidence: 73%
See 1 more Smart Citation
“…Kinetic constants were higher in MM for the lowest initial concentrations of thiocyanate, whereas the opposite behaviour was observed for concentrations higher than 4,000 mg L -1 . Degradation rates between 1 and 87 mg (Lh) -1 were reported for the biodegradation of thiocyanate by specific microorganisms [6,18,19,24] similar to the degradation rates obtained in this work. In fact, only Acremonium strictum showed higher removal rates [19].…”
Section: Utilization Of Nitrogen and Sulphur From Thiocyanatesupporting
confidence: 73%
“…According to studies that focused on thiocyanate biodegradation, 2,500 mg L -1 of thiocyanate were biodegraded in 120 hrs with the co-culture Klebsiella pneumoniae and Ralstonia sp [6], 3,395 mg SCN -L -1 were removed after 7 days by Thiobacillus thioparus THI115 [18] and 970 mg SCN -L -1 were eliminated by Thioalkalivibrio thiocyanodenitrificans [24] after 30-40 days. Considering these results, our system is more efficient in terms of the thiocyanate biodegradation rate, especially when the medium is free of C, N and S sources.…”
Section: Utilization Of Nitrogen and Sulphur From Thiocyanatementioning
confidence: 99%
“…Chemical analysis of sulfur (sulfide, sulfur, thiosulfate and sulfite) and nitrogen (nitrite and ammonium) compounds, and cell protein were performed as described previously (Sorokin et al 2001(Sorokin et al , 2004b. Sulfane atom of polysulfide was analyzed in the same way as free sulfide, i.e.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Differential characteristics of strain XK5 T and other related genera Genera: 1, Woeseia gen. nov. (XK5 T ; data from this study); 2, Thioalkalivibrio (Banciu et al, 2004;Sorokin et al, 2001Sorokin et al, , 2002aSorokin et al, , b, 2003Sorokin et al, , 2004Sorokin et al, , 2012; 3, Natronocella (Sorokin et al, 2007); 4, Thiorhodospira (Bryantseva et al, 1999(Bryantseva et al, , 2010; 5, Thiohalospira (Sorokin et al, 2008). -, Trace amount or not detected; ND, no data available.…”
mentioning
confidence: 99%
“…The almost-complete 16S rRNA gene sequence (1476 bp) was obtained from strain XK5 T and BLAST searches revealed that the novel isolate had highest similarity to Thioalkalivibrio thiocyanodenitrificans DSM 16954 T (92.1 %; Sorokin et al 2004), followed by two other members of the same genus, Thioalkalivibrio sulfidiphilus NCCB 100376 T (91.9 %; Sorokin et al 2012) and Thioalkalivibrio denitrificans DSM 13742 T (91.8 %; Sorokin et al 2001). Except for the above three strains, other published strains showed ,91.0 % sequence similarity with strain XK5 T .…”
mentioning
confidence: 99%